GC-MS studies to map mechanistic aspects of photolytic decomposition of pesticides - Kiss, Attila; Virág, Diána (Acta Agraria Debreceniensis, 2008)
Transformation of pesticides in the environment is a highly complex process affected by different factors. Both biological and physical-chemical factors may play a role in the degradation, whose ratio depends on the actual environmental conditions.Our study aims to reveal specific details of photolytic degradation of pesticides as important soil contaminants. Significance of these studies is enhanced by the fact that pesticide decomposition may contribute to soil degradation, and have harmful biological effects by degrading to toxic products. The toxicity of the examined pesticides is well known, however very little information is available regarding their natural degradation processes, the quality, structure and biological impact of the degradation products.The photolytic degradation of frequently applied pesticides of distinctive types (acetochlor – acetanilide, simazine – triazine, chlorpyrifos – organophosphate, carbendazim – benzimidazole) was investigated. A special, immerseable UV-light source was applied in order to carry out photodegradation. The degradation processes were followed by thin layer chromatography (TLC) and mass spectrometry coupled with gas chromatography (GC/MS). EI mass spectrometry was used to identify the degradation species.Each of the studied pesticides underwent photolytic decomposition, and the detailed mechanism of photolytic transformation was established. At least four degradation species were detected and identified in each case. Loss of alkyl, alkyloxy, amino-alkyl and chloro groups might be regarded as typical decomposition patterns. Deamination occurred at the last stage of decomposition.